Butachlor‐Induced Alterations in Ultrastructure, Antioxidant, and Stress‐Responsive Gene Regulations in Rice Cultivars. Issue 3 (10th February 2017) - Islam, Faisal; Ali, Skhawat; Farooq, Muhammad A.; Wang, Jian; Gill, Rafaqat A.; Zhu, Jinwen; Ali, Basharat; Zhou, Weijun
Abstract : Butachlor is an extensively applied herbicide in paddy fields. However, concerns have been raised about its potential adverse effects on the biochemical and physiological processes of non‐target plants. In the present investigation, butachlor‐induced toxic effects in two rice cultivars, Zhejing 88 (ZJ 88) and Xiushui 134 (XS 134), treated with different butachlor treatments were evaluated. A significant decrease in growth rate, pigment concentration, and chlorophyll fluorescence and alternations in chloroplast structures were observed in both rice cultivars at higher treatment levels. The malfunctioning of antioxidant enzymes, the higher uptake of butachlor, and the downregulation of the putative fatty acid elongase gene suggested severe oxidative damage, which was also indicated by enhanced reactive oxygen species (ROS) formation (H2 O2, O 2 − ), lipid peroxidation, and electrolyte leakage and reduced total soluble protein levels in cultivar ZJ 88 than in cultivar XS 134. However, higher proline accumulation and pyrroline‐5‐carboxylate synthase and GABA‐transaminase transcript levels in ZJ 88 suggested their ameliorative role under butachlor‐induced oxidative stress in the sensitive cultivar. In contrast, the stimulated activation of antioxidant enzymes, glutathione, soluble sugars, and phenolics played a vital role in protection against butachlor stress in cultivar XS 134. Thus, butachlor‐induced oxidative stress tolerance in the resistant cultivar (XS 134) is related to the enhanced activation of different isoforms of antioxidant enzymes and a reduced uptake of butachlor compared to the sensitive cultivar (ZJ 88). The present work provides valuable insights into butachlor‐induced toxicity in rice plants. Abstract : Butachlor induced alterations in morpho‐anatomical, physiological, biochemical, and molecular traits differently in rice cultivars. The variability in the response to the butachlor exposure indicates the existence of cultivar variation in rice population. This suggests that application of resistant cultivar in butachlor contaminated soils could effectively enhance plant growth.